Gamma-Band Activities in Mouse Frontal and Visual Cortex Induced by Coherent Dot Motion - Han, Hio-Been; Hwang, Eunjin; Lee, Soohyun; Kim, Min-Shik; Choi, Jee Hyun (NATURE PUBLISHING GROUP, 2017)
A key question within systems neuroscience is to understand how the brain encodes spatially and temporally distributed local features and binds these together into one perceptual representation. Previous works in animal and human have shown that changes in neural synchrony occur during the perceptual processing and these changes are distinguished by the emergence of gamma-band oscillations (GBO, 30-80 Hz, centered at 40 Hz). Here, we used the mouse electroencephalogram to investigate how different cortical areas play roles in perceptual processing by assessing their GBO patterns during the visual presentation of coherently/incoherently moving random-dot kinematogram and static dots display. Our results revealed that GBO in the visual cortex were strongly modulated by the moving dots regardless of the existence of a global dot coherence, whereas GBO in frontal cortex were modulated by coherence of the motion. Moreover, concurrent GBO across the multiple cortical area occur more frequently for coherently moving dots. Taken together, these findings of GBO in the mouse frontal and visual cortex are related to the perceptual binding of local features into a globally-coherent representation, suggesting the dynamic interplay across the local/distributed networks of GBO in the global processing of optic flow.
Keywords: NEURAL MECHANISMS; NEURONAL SYNCHRONIZATION; OSCILLATORY SYNCHRONY; SPATIAL ATTENTION; PERCEPTION; SCHIZOPHRENIA; POTENTIALS; RESPONSES; PARALLEL; NETWORK